Modeling and simulation of a communication-assisted digital protection scheme for micro-grids. (May 2016) - Mirsaeidi, Sohrab; Said, Dalila Mat; Mustafa, Mohd. Wazir; Habibuddin, Mohd. Hafiz; Ghaffari, Kimia
Abstract: The protection of micro-grid should be in such a way that a safe and secure protection is provided in both grid-connected and stand-alone operation modes. Nevertheless, the function of micro-grid in these two modes creates some new protection problems. During grid-connected operation mode, since micro-grid provides a large short-circuit current to the fault point, the protection can be performed by existing protective devices within the distribution networks, but in islanded mode, fault currents are drastically lower than those of grid-connected mode; hence, the employment of traditional overcurrent-based protective devices in micro-grids is no longer valid. In order to overcome this challenge, different approaches have recently appeared in the literatures. This paper presents a micro-grid protection scheme based on positive-sequence impedance using Phasor Measurement Units (PMUs) and designed Microprocessor- Based Relays (MBRs) along with a digital communication system. The proposed scheme has the ability to protect radial and looped micro-grids against different types of faults with the capability of single-phase tripping. Furthermore, since the MBRs are capable of updating their pickup values (upstream and downstream equivalent positive-sequence impedances of each line) after the first change in the micro-grid configuration (such as transferring from grid-connected to islanded mode and or disconnection of a line, bus, or DG either in grid-connected mode or in islanded mode), they can protect micro-grid lines and buses against subsequent faults. Finally, in order to verify the effectiveness of the suggested scheme and the designed MBR, several simulations have been undertaken by using DIgSILENT PowerFactory and MATLAB software packages.